Pandangan ulama Garut tentang wakaf uang dan wakaf muâaqqat - Hermawan, Wawan (Sekolah Tinggi Agama Islam Negeri Salatiga, 2013)
This paper raises the issue of the opinion of Garut Islamic scholars (ulama) about cash waqf and limited time (muâaqqat) of waqf, two issues of waqf are considered as the new problems of waqf for the Indonesian muslims as opposed to their view before. The findings of this study are as follows: 1) Garut Islamic scholars agree that the law of cash waqf is permitted becouse that cash waqf does not conlict with essence of waqf; 2) There are differences of opinion among Garut scholars relating the law of limited time of waqf. Some of them said that this waqf allowed becouse it does not conflict with the meaning and the esssence of waqf, even charitable opportunites for the community will be greater in the presence of limited waqf. Some other scholars consider that limited time of waqf have violated the essence of waqf to be timeless, forever. However, they still consider that there is virtue of this type of waqf, and still allowed conducted with a note its name is not waqf.